Defining the MIS-TLIF: A Systematic Review of Techniques and Technologies Used by Surgeons Worldwide. Issue 2 (April 2020) - Lener, Sara; Wipplinger, Christoph; Hernandez, R. Nick; Hussain, Ibrahim; Kirnaz, Sertac; Navarro-Ramirez, Rodrigo; Schmidt, Franziska Anna; Kim, Eliana; Härtl, Roger
Study Design: Systematic review. Objective: To date there is no consensus among surgeons as to what defines an MIS-TLIF (transforaminal lumbar interbody fusion using minimally invasive spine surgery) compared to an open or mini-open TLIF. This systematic review aimed to examine the MIS-TLIF techniques reported in the recent body of literature to help provide a definition of what constitutes the MIS-TLIF, based on the consensus of the majority of surgeons. Methods: We created a database of articles published about MIS-TLIF between 2010 and 2018. We evaluated the technical components of the MIS-TLIF including instruments and incisions used as well the order in which key steps are performed. Results: We could identify several patterns for MIS-TLIF performance that seemed agreed upon by the majority of MIS surgeons: use of paramedian incisions; use of a tubular retractor to perform a total facetectomy, decompression, and interbody cage implantation; and percutaneous insertion of the pedicle-screw rod constructs with intraoperative imaging. Conclusion: Based on this review of the literature, the key features used by surgeons performing MIS TLIF include the use of nonexpandable or expandable tubular retractors, a paramedian or lateral incision, and the use of a microscope or endoscope for visualization. Approaches using expandable nontubular retractors, those that require extensive subperiosteal dissection from the midline laterally, or specular-based retractors with wide pedicle to pedicle exposure are far less likely to be promoted as an MIS-based approach. A definition is necessary to improve the communication among spine surgeons in research as well as patient education.